The voyage of turtle Rex - Cyrus, Kurt. (Boston : Harcourt Children's Books, 2011)
Follows the life of a giant prehistoric sea turtle from her egg and into the treacherous waters of the ocean, where she must avoid larger sea creatures until she is full-grown and can return to the shore and lay eggs of her own.
Pub Weekly
School Library Journal starred
Wilson's Children
Horn Book, October 2011
Kirkus Starred, March 2011
Library Media Connection, October 2011
Keywords: Animals, Fossil -- Juvenile fiction; Marine animals, Fossil -- Juvenile fiction; Sea turtles -- Juvenile fiction; Turtles -- Juvenile fiction; Marine animals, Fossil -- Fiction; Prehistoric animals -- Fiction; Sea turtles -- Fiction; Stories in rhyme; Turtles -- Fiction; Fossils -- Fiction; Marine animals -- Fiction; Prehistoric animals -- Fiction; Sea turtles -- Fiction; Stories in rhyme; Turtles -- Fiction; Picture books for children